Sustainable thermal insulation of geopolymer blocks using solid waste: palm oil ash and palm oil clinker - Hawa, Abideng; Salaemae, Preecha (Journal of Engineering and Technological Sciences, 2025)
This paper has analyzed the thermal insulation of geopolymer blocks prepared using palm oil ash (POA) with the addition of alumina powder (AP) and field Para rubber latex (FPRL). The block samples were set up to use 3 and 5 channels and channel width of 2 and 4 mm each with geopolymer binder as POA (containing 5% FPRL and 0%, 2.5%, 5%, 7.5%, and 10% AP) and POC as fine aggregate. The compressive strength, water absorption, bulk density of the geopolymer mortars and thermal conductivity of geopolymer blocks were explored. The AP and FPRL had minimal impact on the compressive strength of the geopolymer mortars and the greater the amount of AP the less water was absorbed. Thermal conductivity of 4 mm wide channel geopolymer blocks was lower than that of 2 mm wide channel blocks and 5 channels blocks had lower thermal conductivity in comparison to 3 channel blocks. The geopolymer blocks had low thermal conductivity relative to the commercial concrete blocks. This study offers valuable information to the application of geopolymers made of POA with FPRL and AP to produce geopolymer materials, POC as a fine aggregate to produce green building materials with enhanced thermal insulation.